高中生海洋科學素養及迷思概念評量分析 Marine Science Literacy and Misconceptions among Senior High School Students - 羅綸新 Lwun-Syin Lwo; 張正杰 Cheng-Chieh Chang; 童元品 Yuan-Ping Tung; 楊文正 Wen-Cheng Yang (National Taiwan Normal University, 2013)
本研究旨在：一、應用概念圖命題模式及開放性問答評量高中生海洋科學概念與素養之現況。二、以問卷試題診斷高中生海洋科學迷思概念之情形。研究以基隆市5 所公立高級中學學生為對象，共計發出361 份問卷，有效樣本346 份，回收率為96%。研究結果顯示：一、高中生在海洋科學概念詞彙運用前三名為暖化、地震及地球。二、高中生在海洋科學概念詞彙運用產生迷思的三大詞彙為生質能源、黑潮及親潮。三、高中生海洋概念以知識面向的概念最高。四、高中生在海洋科學迷思概念試題評量中，平均答對率只有53%。五、黑潮得名緣由為高中生在海洋科學迷思概念評量中答對率最低的題目，僅有16%。六、「瞭解冰期與間冰期海平面的升降，對全球生物與自然環境可能造成影響」為高中生最常帶有迷思概念的能力指標。研究的結果可供我國海洋教育相關人員及高中教師參考，以提升海洋教育實施之成效與國民海洋科學素養。 The purposes of this study were to examine the literacy of senior high school students regarding marine-science concepts by using the concept-map method (open-ended tasks) and an open-ended question, and to assess their misconceptions about marine science. A survey was conducted among students from five senior high schools in northern Taiwan. A total of 361 questionnaires were distributed and a validity count of 346 was returned. The results of this study were as follows: (1) The terms "warming," "earthquake," and "earth" were most commonly used by students to express marine-science concepts. (2) The terms "bioenergy," "Kuroshio Currents," and "Oyashio Currents" caused the most confusion among students. (3) The marine concepts described by the students were more in cognitive domain, than in attitude and affective domains. (4) The students' average correct response rate in the marine-science misconception assessment was 53%. (5) The term "Kuroshio Currents" received the lowest score (16% correct) in the marine-science misconception assessment of students. (6) Students typically misconstrued the following marine-science competence index: "Increases and decreases in sea levels during glacial and interglacial periods may influence global biology and the natural environment." The results of this study can assist marine-science researchers and senior high school teachers to improve the quality and effectiveness of marine-science education and promote marine-science literacy.